Length/weight relationship and condition factor of Macrobrachium jelskii (Miers, 1877) and M. brasiliense (Heller, 1862) (Decapoda, Palaemonidae) in two locations in the state of São Paulo - Taddei, Fabiano Gazzi; Herrera, Daphine Ramiro; Davanso, Thiago Maia; Silva, Thiago Elias Da; Costa, Rogério Caetano Da; Fransozo, Adilson (Sociedade Brasileira de Carcinologia, 2017)
Abstract This study describes the weight vs. carapace length relationship and provides the total and monthly condition factor values for populations of Macrobrachium jelskii (Miers, 1977) and M. brasiliense (Heller, 1868) occurring in southeastern Brazil. The biological characteristics were compared and related to the climatic environmental factors between the two areas. Our investigation sampled M. jelskii from the Barra Mansa Dam, Mendonça, SP, a semilotic environment with greater resilience than the Talhadinho Stream, Talhado, SP, a lotic environment where specimens of M. brasiliense were captured. Individuals were classified according to sex and measured at the carapace length (CL) and weighed (WE). The relationship WE/CL was analyzed by dispersion diagrams of the empirical points, which were set to the power function (WE = a.CL b ). Values of the mean condition factor were compared monthly. In total, 1493 individuals of M. jelskii and 843 individuals of M. brasiliense were captured. Analyses of the constant allometry revealed that both sexes of M. jelskii, as well as females of M. brasiliense grow proportionately more in size than weight. The results concerning the morphometric aspects studied in both species suggest an association with the reproductive processes.
Keywords: Caridea; ecology; growth; limnology; reproduction; São Paulo State